Modification and Application Study of Activated Natural Zeolite for the Treatment of Liquid Waste from Chemical Laboratory - Liqanatul Putri Sholikah; Sumari Sumari; Yuneta Dwi Yunisari (Jurnal Kimia Sains dan Aplikasi, 2023)
Natural zeolite from Malang Regency is a raw material that can be used as an adsorbent for heavy metal waste. However, this natural zeolite needs activation and optimization to be utilized maximally as an adsorbent. This study was conducted for both physical and chemical activation of natural zeolite. Characterization results of XRD indicated that the natural zeolite possesses crystalline phases and is of the mordenite type. Based on the XRF results, the Si/Al ratio increased from 5.768 to 6.119 after activation. Based on the characterization results using the BET method with SAA analysis, the surface area of non-activated natural zeolite was determined to be 20.8045 m²/g, while activated natural zeolite had a surface area of 137.8196 m²/g. Results of the adsorption study in treating liquid laboratory waste using simulated Pb and Cr metal wastes demonstrated that activated natural zeolite performed more effectively as an adsorbent than non-activated natural zeolite. The adsorbent’s optimum mass was 0.3 grams, resulting in an adsorption percentage of 97.43% for Pb and 97.56% for Cr, with a contact time of 30 minutes at pH 6. The adsorption kinetics of Pb and Cr metals were described using a pseudo-second-order rate equation. The adsorption of Pb and Cr was depicted using the Langmuir equation, indicating the monolayer formation on the homogenous adsorbent surface during the adsorption process. The activated natural zeolite has the potential to be employed as an independent adsorbent in the treatment of heavy metal waste.